Evaluation of state support of APK industries ("Journal "U". Economy. Management. Finance.", 2025)
The study assesses the effectiveness of state support for APK, identifies problems and suggests ways to increase the sustainability of the industry.
Keywords: state support; agro-industrial complex; efficiency; sustainable development; food security